Beiträge zur Kenntnis mitteleuropäischer Wanzen (Heteroptera). - Polentz, Georg (Contributions to Entomology = Beiträge zur Entomologie, 1958)
There are recorded species or formae of Heteroptera rare or recently described from Anhalt, Bavaria, Westphalia, Hessia, Hanover, the Kyffhäuser, and the Hartz. A second record is given of the rare species Lygus gemellatus v. innotatus Pol. as like as notes on the life-history of Phytocoris intricatus Flor, P. ulmi L., and Placochilus seladonicus Fall. An abnormity of the antennae in Phytocoris intricatus Flor, is described.